A role for the endocannabinoid enzymes monoacylglycerol and diacylglycerol lipases in cue‐induced cocaine craving following prolonged abstinence. (25th January 2021) - Mitra, Swarup; Gobira, Pedro H.; Werner, Craig T.; Martin, Jennifer A.; Iida, Madoka; Thomas, Shruthi A.; Erias, Kyra; Miracle, Sophia; Lafargue, Charles; An, Chunna; Dietz, David M.
Abstract: Following exposure to drugs of abuse, long‐term neuroadaptations underlie persistent risk to relapse. Endocannabinoid signaling has been associated with drug‐induced neuroadaptations, but the role of lipases that mediate endocannabinoid biosynthesis and metabolism in regulating relapse behaviors following prolonged periods of drug abstinence has not been examined. Here, we investigated how pharmacological manipulation of lipases involved in regulating the expression of the endocannabinoid 2‐AG in the nucleus accumbens (NAc) influence cocaine relapse via discrete neuroadaptations. At prolonged abstinence (30 days) from cocaine self‐administration, there is an increase in the NAc levels of diacylglycerol lipase (DAGL), the enzyme responsible for the synthesis of the endocannabinoid 2‐AG, along with decreased levels of monoacylglycerol lipase (MAGL), which hydrolyzes 2‐AG. Since endocannabinoid‐mediated behavioral plasticity involves phosphatase dysregulation, we examined the phosphatase calcineurin after 30 days of abstinence and found decreased expression in the NAc, which we demonstrate is regulated through the transcription factor EGR1. Intra‐NAc pharmacological manipulation of DAGL and MAGL with inhibitors DO‐34 and URB‐602, respectively, bidirectionally regulated cue‐induced cocaine seeking and altered the phosphostatus of translational initiation factor, eIF2α. Finally, we found that cocaine seeking 30 days after abstinence leads to decreased phosphorylation of eIF2α and reduced expression of its downstream target NPAS4, a protein involved in experience‐dependent neuronal plasticity. Together, our findings demonstrate that lipases that regulate 2‐AG expression influence transcriptional and translational changes in the NAc related to drug relapse vulnerability. Abstract : Endocannabinoid lipases and downstream EGR1‐mediated transcriptional pathways are dysregulated in the NAc following prolonged abstinence from cocaine self‐administration. Pharmacological manipulations of the endocannabinoid lipases result in altered behavioral plasticity.